Entornos Virtuales 3D Con Juegos De Rol Y Diálogos Para Desarrollar La Comunicación Oral Del Idioma Inglés - Salazar Calderón Edison Hernán; Armas Pesántez Paul Rolando; Armas Pesántez Washington Geovanny; Guadalupe Bravo Luis Oswaldo; Orozco Yánez Gabriel Isaac; Allauca Peñafiel Marcelo Eduardo (European Scientific Journal, ESJ, 2017)
The present research aims at the application of a conversational English course in 3D virtual environments, to develop oral communication of the language in the students of the sixth level "G" at the Faculty of Engineering of the National University of Chimborazo, from March to August of 2014, inasmuch as, little interest in and outside the classroom was detected, which inhibited the learning process. Therefore, the use of listening and speaking skills was proposed, using communicative techniques such as role play and discussion. The development of the research was based on a quasi-experimental and qualitative design, applied type, causal, in situ and bibliographic. The method used was the hypothetical - deductive one that allowed to verify that the oral communication of the English language was developed. It was essential to develop the activities contained in the conversational course, which allowed the collection of information through evaluations with an observation sheet and qualifications scale applied to an experimental group, represented by the sample in two scenarios: before and after applying communicative strategies; the same ones that were tabulated, analyzed, interpreted and compared, these determined that the techniques, role play and dialogue, allowed to develop the oral language skill of the students through the English course.